Evlaution of Different Suturing Techniques in Deep Third Molar Surgery: An Original Research - Fawaz Abdul Hamid Baig; Sunil Kumar Beniwal; P. V. Samir; Gokul Venkateshwar; Mamta Singh; Siva Kumar Pendyala (Wolters Kluwer Medknow Publications, 2024)
Purpose: The purpose of this study was to compare the efficacy of various suturing methods used in deep third molar extraction procedures. Methods: A total of four suturing method groups-simple interrupted, horizontal mattress, vertical mattress, and figure-of-eight-were randomly allocated to 100 patients having deep third molar surgery. Assessments were conducted on wound healing, operation time, intraoperative problems, postoperative pain scores, swelling measures, and patient satisfaction questionnaires. Appropriate tests were used for statistical analysis, with P < 0.05 being regarded as significant. Results: Compared to other procedures, the figure-of-eight technique showed better results in terms of postoperative pain scores, swelling measures, wound healing percentages, and patient satisfaction (P < 0.05). There was no discernible difference in the operating time or intraoperative problems between the groups. Conclusion: In conclusion, there seems to be a benefit to using the figure-of-eight suturing approach for deep third molar surgery in terms of improved postoperative results and patient satisfaction. It is recommended that clinicians give this strategy some thought to improve patient care and surgical results.